Micro‐geographic shift between negligible and actuarial senescence in a wild snake. Issue 11 (14th September 2020) - Tully, Thomas; Le Galliard, Jean‐François; Baron, Jean‐Pierre
Abstract: While it has long been known that species have contrasted life expectancy (pace of mortality) and generation time (pace of reproduction), recent studies have also uncovered that the shape of adult age trajectories of mortality and reproduction can vary remarkably among species along a continuum of senescence ranging from strong deterioration (senescence), insignificant deterioration (negligible senescence) to improvement with advancing age (negative senescence). As for many long‐lived ectotherms with asymptotic growth and increasing reproductive output with age, snakes are good candidates for negligible senescence to occur. Yet, intraspecific variation in the pace and shape of actuarial and reproductive senescence across wild populations of these species remains to be explored. Here, we used 37 years of mark–recapture data in two nearby habitats inside a meadow viper Vipera ursinii population to quantify life expectancies, generation times and the shape of actuarial and reproductive senescence. Female vipers maintained stable reproductive performances at old ages, even when accounting for the predicted increase of fertility with body size, providing evidence for negligible reproductive senescence in both habitats. Males had a higher adult mortality and a shorter life expectancy on average than females and actuarial senescence shifted from negligible senescence in the optimal habitat to strong senescence in the sub‐optimal habitat. Overall, these results demonstrate that micro‐geographic environmental variation can generate qualitative shifts in actuarial senescence patterns. This highlights that taking into account the within‐species plasticity of age‐dependent trajectories could prove useful in better understanding what determines the evolution of life‐history age trajectories. Abstract : Old meadow vipers can maintain a high reproductive output and a high survival in the wild (negligible senescence). But the pattern of actuarial senescence is plastic and can shift from negligible senescence to strong senescence at a micro‐geographic scale. Photo by Matthieu Berroneau. Résumé: La longévité et la manière de vieillir varient grandement entre espèces. Chez certaines espèces, la survie et la reproduction déclinent avec l'âge : les individus souffrent de sénescence. Chez d'autres, les vieux individus maintiennent des performances reproductives et de survie similaires à celles des jeunes : la sénescence est alors dite négligeable. Enfin, la sénescence peut être négative quand la survie des adultes ou leur reproduction s'améliorent avec l'âge. Les formes des trajectoires de mortalité et de reproduction avec l'âge sont encore mal connues chez les serpents, mais la théorie évolutive prédit une sénescence négligeable chez les espèces qui, comme les serpents, continuent à grandir à l'âge adulte et dont les femelles produisent des portées dont l'effectif augmente avec la taille corporelle de la mère. Nous avons exploité ici 37 années de données de capture‐marquage‐recapture de vipères d'Orsini, Vipera ursinii ursinii, dans deux habitats voisins d'une petite population isolée du Sud‐Est de la France pour quantifier l'espérance de vie, les temps de génération et les formes de la sénescence de survie et de la sénescence reproductrice. Nous montrons que les vipères femelles parviennent à maintenir de bonnes performances reproductives même à des âges avancés, illustrant une sénescence reproductrice négligeable dans cette population. Nous montrons aussi que la forme de la sénescence de survie varie fortement à une très petite échelle géographique : dans l'habitat optimal, la survie adulte des vipères demeure stable quel que soit leur âge alors qu'à quelques centaines de mètres, dans un habitat moins favorable, les vipères subissent une forte sénescence de survie. Ces résultats démontrent que de forts changements qualitatifs dans les profils de sénescence peuvent être observés à une échelle spatiale réduite. Cette plasticité intra‐spécifique de la sénescence offre de nouvelles perspectives pour mieux comprendre ce qui détermine l'évolution de la sénescence.